Building information modelling - BIM na arquitectura, construção e pré-fabricação - David Alexandre Martins Vasconcelos (2013)
The following work has the purpose to expose a current and urgent subject. The tackled topic "BIM in Architecture, Construction and Prefabrication", is present in this essay due to the interest in working method of Building Information Modeling - BIM, for with architects, builders and the design and creation of prefabricated elements. The analysis tries to understand how the architecture design can be worked in this system, so that the architect may have interoperability between engineers and builders - AEC. This union will give new capabilities to projects of various professionals, analysed in a common environment suggesting greater criticism and analysis among various stakeholders. The reflection of the adoption by the architecture workshops by a BIM system brings an increase in production work in the architectural design, which is very due to the ability of BIM systems work with more dimensions of which we are used to, in the case of 3D ( Three Dimensions), 4D (Three dimensions + time) and 5D (Three dimensions + time + costs). The architectural design combined with this new system will turn it more complex and insightful in the production of a building system, as well as the creation of prefabricated elements which have greater ease of management when inserted in these work environments. The result of this work is expressed in the case studies of international and national context, in order to be able to have a better view of what these systems can give to the Architect, Engineer and Builder. After the analysis of these case studies it´s demonstrated in a personal project which measures are necessary for us to ally the several AEC stakeholders, and in which stage each one goes in, but always in agreement with the Architect´s point of view.